دراسة سميّة المبيدين بروبارجيت و أبامكتين للأكاروسين Tetranychus urticae Koch و Panonychus ulmi Koch (Acari:Tetranychidae) وللمفترس الأكاروسي Amblyseius spp (Acari:Phytoseiidae) في بساتين التفاح - حلّوم, منذر; قرحيلي, صفاء (Latakia University Journal -Biological Sciences Series, 2019)
قُدّرت سميّة المبيدين الأكاروسيين بروبارجيت 57 ECأبامكتين 1.8 EC للأكاروسين: العنكبوتي ذو البقعتين Tetranychus urticae Koch (Acari:Tetranychidae) و الأحمر الأوربي ( Panonychus ulmi Koch (Acari: Tetranychidae وللمفترس الأكاروسي Amblyseius spp (Acari: Phytoseiidae) .كان البروبارجيت ضعيف السمية لـ Amblyseius spp وعالي السمية لـ T.urticae, P.ulmi.أما سمية الأبامكتين فكانت متوسطة لـ Amblyseius spp بينما كانت مرتفعة لـT.urticae, P.ulmi.سُجلّت أعداد متقاربة منT.urticae, P.ulmi في المعاملات الثلاث بعد 25 يوماً من المعاملة؛ تزامن ذلك مع أعداد أعلى من المفترس الأكاروسي Amblyseius spp في الشاهد غير المعامل بمبيد مقارنة بأعداده في معاملتي المبيدين. The relative toxicity of two acaricides: propargite 57 EC and abamectin 1.8 EC to Tetranychus urticae Koch (Acari:Tetranychidae), Panonychus ulmi Koch (Acari: Tetranychidae) and the predatory mite Amblyseius spp (Acari: Phytoseiidae) has been evaluated in apple orchards under field conditions. Propargite has been slightly toxic to the Amblyseius spp and very toxic to T.urticae, and P.ulmi. Abamectin has been moderately toxic to Amblyseius spp and very toxic to T.urticae and P.ulmi. After 25 days of treatment, the same numbers for T.urticae and P.ulmi recur in the three treatments; but the figures for Amblyseius spp have been greater than those in the two acaricides treatments.